A process evaluation of a comprehensive school based injury prevention programme. (1st March 2011) - Chapman, R; Buckley, L; Sheehan, M; Shochet, I
Abstract : A process evaluation enables understanding of critical issues that can inform the improved, ongoing implementation of an intervention programme. This study describes the process evaluation of a comprehensive, multi-level injury prevention programme for adolescents. The programme targets change in injury associated with violence, transport and alcohol risks and incorporates two primary elements: an 8-week, teacher delivered attitude and behaviour change curriculum for Grade 8 students; and a professional development programme for teachers on school level methods of protection, focusing on strategies to increase students' connectedness to school. A comprehensive process evaluation methodology was used, including assessments of dose, adherence, quality of process and participant responsiveness with teachers and Grade 8 students at four Australian high schools. Programme dose, adherence and quality of curriculum delivery were assessed through independent observations. The observer also rated the degree to which teachers used connectedness strategies in class, following participation in professional development. Teachers' responsiveness to the professional development element was assessed through surveys immediately following the training, and through focus groups for in-depth information. Student focus groups also enabled insight into their responsiveness to the programme and their perceptions of teachers' use of connectedness strategies. The results of this research provide an understanding of the application of a process evaluation to a comprehensive injury prevention programme and enable insight into the means by which the programme may be better implemented to maximise effect and sustainability. The findings also provide insight into the potential value of school connectedness in adolescent injury prevention.